Aqueous emulsions from oxidized polyethylene waxes stabilized with non-ionic agents - Krysztofik, Łukasz; Osowiecka, Blandyna; Liszyńska, Barbara; Zieliński, Janusz; Zakarzecki, Marcin (Polimery, 2022)
The stable emulsions from oxidized polyethylene waxes with the use of various non-ionic emulsifiers from the group of fatty alcohol ethoxylates with HLB in the range 11−16 were obtained. The effectiveness of the emulsification was assessed by measuring the dispersed phase particle size and the emulsion stability. The highest emulsifying efficiency was achieved using a non-ionic emulsifier with HLB of 16.3.